From Hashtag to High School: How Viral Tweets Are Inspiring Young Scientists To Embrace STEM - Jocelyn E. Swift (American Society for Microbiology, 2020)
Social media is an increasingly important professional tool for scientists. In particular, scientists use their social media profiles to communicate science and build communities with like-minded scientists and nonscientists. These networks include journalists who can amplify social media science communication, disseminating it to new audiences on- and offline. Our experience with an outreach project where Peeps marshmallows were inoculated with diverse fungi, which we called #FungalPeeps, has demonstrated that these networks can be an effective conduit between researchers and high school students. Following popular science journalism, #FungalPeeps, a project initiated at West Virginia University, inspired a mycology research project in Notre Dame High School in San Jose, California. Herein, we describe how this connection between academia, journalists, and the high school classroom happened, and how everyone involved benefited from this educational collaboration. We further suggest ways that modern social media networks could be leveraged to incorporate more such practical learning experiences into progressive science curricula to better cultivate young STEM scientists.